Epileptic patients with de novo STXBP1 mutations: Key clinical features based on 24 cases. (29th October 2015) - Di Meglio, Chloé; Lesca, Gaetan; Villeneuve, Nathalie; Lacoste, Caroline; Abidi, Affef; Cacciagli, Pierre; Altuzarra, Cécilia; Roubertie, Agathe; Afenjar, Alexandra; Renaldo‐Robin, Florence; Isidor, Bertrand; Gautier, Agnes; et al.
Summary: Objective: Mutations in the syntaxin binding protein 1 gene ( STXBP1 ) have been associated mostly with early onset epileptic encephalopathies (EOEEs) and Ohtahara syndrome, with a mutation detection rate of approximately 10%, depending on the criteria of selection of patients. The aim of this study was to retrospectively describe clinical and electroencephalography (EEG) features associated with STXBP1 ‐related epilepsies to orient molecular screening. Methods: We screened STXBP1 in a cohort of 284 patients with epilepsy associated with a developmental delay/intellectual disability and brain magnetic resonance imaging (MRI) without any obvious structural abnormality. We reported on patients with a mutation and a microdeletion involving STXBP1 found using array comparative genomic hybridization (CGH). Results: We found a mutation of STXBP1 in 22 patients and included 2 additional patients with a deletion including STXBP1 . In 22 of them, epilepsy onset was before 3 months of age. EEG at onset was abnormal in all patients, suppression‐burst and multifocal abnormalities being the most common patterns. The rate of patients carrying a mutation ranged from 25% in Ohtahara syndrome to <5% in patients with an epilepsy beginning after 3 months of age. Epilepsy improved over time for most patients, with an evolution to West syndrome in half. Patients had moderate to severe developmental delay with normal head growth. Cerebellar syndrome with ataxic gait and/or tremor was present in 60%. Significance: Our data confirm that STXBP1 mutations are associated with neonatal‐infantile epileptic encephalopathies. The initial key features highlighted in the cohort of early epileptic patients are motor seizures either focal or generalized, abnormal initial interictal EEG, and normal head growth. In addition, we constantly found an ongoing moderate to severe developmental delay with normal head growth. Patients often had ongoing ataxic gait with trembling gestures. Altogether these features should help the clinician to consider STXBP1 molecular screening.